Comparison of Altmetrics across Multiple Disciplines: Psychology, History, and Linguistics - Htoo, Tint Hla Hla (2017)
Since their emergence in 2010, altmetrics as new indicators of research impact receive considerable attention from scientometricians and various other parties including librarians, who have long been providing citation analysis and bibliometric services in academic and research institutions. Despite their rapid popularity, the validity of altmetrics in research evaluation is not yet clear. One way of assessing a new metric for its suitability in research evaluation is to find out its correlation with an established source of evidence. This study investigates the correlation between altmetrics and citation count in Psychology, History and Linguistics disciplines. In addition, the study also explores the coverage of altmetric measures in each of these disciplines to identify the presence and potential usefulness of different altmetric measures in different disciplines. Altmetrics data from altmetrics.com and citation data from Web of Science database are used for articles published between 2010 and 2012 in top 70 journals of Psychology and Linguistics disciplines and 53 journals of History discipline. Out of 10, 5 metrics (Twitter, Facebook, Blogs, Mendeley and CiteULike) are found to have significant correlation with citation in Psychology while only 2 metrics (Mendeley and Twitter) are in Linguistic and History. In terms of coverage, discipline with higher citation rate (Psychology) attracts higher altmetric coverage while disciplines with lower citation rate (Linguistics and History) attract lower altmetric coverage. Of the three disciplines studied, Psychology is found to be the most likely candidate where altmetrics could be meaningful measures.